Preparation and in vivo evaluation of cationic elastic liposomes comprising highly skin-permeable growth factors combined with hyaluronic acid for enhanced diabetic wound-healing therapy. (15th July 2017) - Choi, Jeong Uk; Lee, Seong Wook; Pangeni, Rudra; Byun, Youngro; Yoon, In-Soo; Park, Jin Woo
Graphical abstract: Abstract: To enhance the therapeutic effects of exogenous administration of growth factors (GFs) in the treatment of chronic wounds, we constructed GF combinations of highly skin-permeable epidermal growth factor (EGF), insulin-like growth factor-I (IGF-I), and platelet-derived growth factor-A (PDGF-A). We genetically conjugated a low-molecular-weight protamine (LMWP) to the N-termini of these GFs to form LMWP-EGF, LMWP-IGF-I, and LMWP-PDGF-A. Subsequently, these molecules were complexed with hyaluronic acid (HA). Combinations of native or LMWP-fused GFs significantly promoted fibroblast proliferation and the synthesis of procollagen, with a magnification of these results observed after the GFs were complexed with HA. The optimal proportions of LMWP-EGF, LMWP-IGF-I, LMWP-PDGF-A, and HA were 1, 1, 0.02, and 200, respectively. After confirming the presence of a synergistic effect, we incorporated the LMWP-fused GFs-HA complex into cationic elastic liposomes (ELs) of 107 ± 0.757 nm in diameter and a zeta potential of 56.5 ± 1.13 mV. The LMWP-fused GFs had significantly improved skin permeation compared with native GFs. The in vitro wound recovery rate of the LMWP-fused GFs-HA complex was 23% higher than that of cationic ELs composed of LMWP-fused GFs alone. Moreover, the cationic ELs containing the LMWP-fused GFs-HA complex significantly accelerated the wound closure rate in a diabetic mouse model and the wound size was maximally decreased by 65% and 58% compared to cationic ELs loaded with vehicle or native GFs-HA complex, respectively. Thus, topical treatment with cationic ELs loaded with the LMWP-fused GFs-HA complex synergistically enhanced the healing of chronic wounds, exerting both rapid and prolonged effects. Statement of Significance: We believe that our study makes a significant contribution to the literature, because it demonstrated the potential application of cationic elastic liposomes as topical delivery systems for growth factors (GFs) that have certain limitations in their therapeutic effects (e.g., low percutaneous absorption of GFs at the lesion site and the requirement for various GFs at different healing stages). Topical treatment with cationic elastic liposomes loaded with highly skin-permeable low-molecular-weight protamine (LMWP)-fused GFs-hyaluronic acid (HA) complex synergistically enhanced the healing of diabetic wounds, exerting both rapid and prolonged effects.